Analisis Pengaruh Program Training dan Pengembangan Karier terhadap Kinerja Karyawan pada Legian Beach Hotel - Putu Melani; I Gusti Ngurah Sanjaya; Yulia Tria Hapsari (Ikatan Da'i Indonesia, 2026)
This study aims to examine the influence of Training Programs and Career Development on Employee Performance at Legian Beach Hotel. The study was motivated by the importance of improving employee performance in the hospitality industry, where service quality plays a vital role. This research employed a quantitative approach using an associative method. The population consisted of 293 employees of Legian Beach Hotel, while the sample included 75 respondents determined using the Slovin formula. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of the Statistical Package for the Social Sciences (SPSS). The results showed that Training Programs had a positive and significant effect on Employee Performance, with a t-value of 6.324 and a significance value of 0.000. Career Development also had a positive and significant effect on Employee Performance, with a t-value of 2.062 and a significance value of 0.043. Simultaneously, Training Programs and Career Development had a positive and significant effect on Employee Performance, with an F-value of 76.815 and a significance value of 0.000. The coefficient of determination (R²) was 0.681, indicating that Training Programs and Career Development explained 68.1% of the variation in Employee Performance, while the remaining 31.9% was influenced by other factors outside the scope of this study. The findings indicate that employee performance can be improved through effective training programs and well-structured career development opportunities. Therefore, Legian Beach Hotel is recommended to continuously improve the quality of its training programs and provide a clear career development system to support optimal employee performance.